Stem‐cell therapy for dilated cardiomyopathy: a pilot study evaluating retrograde coronary venous delivery. (3rd June 2013) - Pogue, B.; Estrada, A. H.; Sosa‐Samper, I.; Maisenbacher, H. W.; Lamb, K. E.; Mincey, B. D.; Erger, K. E.; Conlon, T. J.
Abstract : Objective: To evaluate retrograde coronary venous stem‐cell delivery for Dobermanns with dilated cardiomyopathy. Methods: Retrograde coronary venous delivery of adipose‐derived mesenchymal stem cells transduced with tyrosine mutant adeno‐associated virus 2 to express stromal‐derived factor‐1 was performed in Dobermanns with dilated cardiomyopathy. Cases were followed for 2 years and electrocardiograms (ECG), echocardiograms and Holter monitoring were performed. Results: Delivery of cells was feasible in 15 of 15 dogs. One dog died following the development of ventricular fibrillation 24 hours after cell delivery. The remaining 14 dogs were discharged the following day without complications. Echocardiographic measurements of left ventricular size and function showed continued progression of disease. On the basis of Kaplan–Meier product limit estimates, median survival for dogs following stem‐cell delivery was 620 days (range of 1–799 days). When including only the occult‐dilated cardiomyopathy population and excluding those dogs already in congestive heart failure, median survival was 652 days (range of 46–799 days). Clinical Significance: Retrograde venous delivery of tyrosine mutant adeno‐associated virus 2‐stromal‐derived factor‐1 adipose‐derived mesenchymal stem cells appears safe. Stem‐cell therapy in dogs with occult‐dilated cardiomyopathy does not appear to offer advantage compared to recently published survival data in similarly affected Dobermanns.